Anne Woolliams: Method of classical ballet Book review - Freeman, Frank (Dance Books Ltd., Alton,Hampshire (UK), 2006)
PALABRAS CLAVE: Anne Woolliams.
Anne Woolliams, edited by Akiko Yuzurihara, K. Kieser Verlag, Munich, 2006.